Bifunctional Oxygen Electrocatalyst of Mesoporous Ni/NiO Nanosheets for Flexible Rechargeable Zn–Air Batteries - Liu, Peitao; Ran, Jiaqi; Xia, Baorui; Xi, Shibo; Gao, Daqiang; Wang, John (Nano-Micro Letters, 2020)
One approach to accelerate the stagnant kinetics of both the oxygen reduction and evolution reactions (ORR/OER) is to develop a rationally designed multiphase nanocomposite, where the functions arising from each of the constituent phases, their interfaces, and the overall structure are properly controlled. Herein, we successfully synthesized an oxygen electrocatalyst consisting of Ni nanoparticles purposely interpenetrated into mesoporous NiO nanosheets (porous Ni/NiO). Benefiting from the contributions of the Ni and NiO phases, the well-established pore channels for charge transport at the interface between the phases, and the enhanced conductivity due to oxygen-deficiency at the pore edges, the porous Ni/NiO nanosheets show a potential of 1.49 V (10 mA cm−2) for the OER and a half-wave potential of 0.76 V for the ORR, outperforming their noble metal counterparts. More significantly, a Zn–air battery employing the porous Ni/NiO nanosheets exhibits an initial charging–discharging voltage gap of 0.83 V (2 mA cm−2), specific capacity of 853 mAh g−1Zn at 20 mA cm−2, and long-time cycling stability (120 h). In addition, the porous Ni/NiO-based solid-like Zn–air battery shows excellent electrochemical performance and flexibility, illustrating its great potential as a next-generation rechargeable power source for flexible electronics. Highlights: 1 An oxygen electrocatalyst consisting of Ni nanoparticles interpenetrated in porous NiO nanosheets was successfully synthesized. 2 The liquid Zn–air battery reveals a large open-circuit potential of 1.47 V, the maximum power density at 225 mW cm−2, and excellent device stability of over 120 h. 3 The flexible solid-like rechargeable Zn–air battery shows excellent stability (no evident weakening after 240 cycles) and bendability.